2017
DOI: 10.1515/pjct-2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

Purification of the gas after pyrolysis in coupled plasma-catalytic system

Abstract: Gliding discharge and coupled plasma-catalytic system were used for toluene conversion in a gas composition such as the one obtained during pyrolysis of biomass. The chosen catalyst was G-0117, which is an industrial catalyst for methane conversion manufactured by INS Pulawy (Poland). The effects of discharge power, initial concentration of toluene, gas fl ow rate and the presence of the bed of the G-0117 catalyst on the conversion of C 7 H 8 , a model tars compounds were investigated. Conversion of coluene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
(7 reference statements)
1
16
1
Order By: Relevance
“…Toluene was used as a model of tar compounds. The conversion of toluene was investigated in a three-phase gliding discharge reactor described previously at normal pressure (Figure ). The 15 mm catalyst bed was located above the end of the electrodes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toluene was used as a model of tar compounds. The conversion of toluene was investigated in a three-phase gliding discharge reactor described previously at normal pressure (Figure ). The 15 mm catalyst bed was located above the end of the electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…A homogeneous nonthermal plasma and a plasma-catalytic system have been widely used for many environmental technologies. The plasma conversion of toluene is investigated by many research groups all over the world. In the coupled plasma-catalytic system, high conversion of toluene and other volatile organic compounds (VOCs) was obtained and the activity of the catalyst was stable. , This may suggest that the use of active catalysts operating in the plasma of gliding discharge can be successfully implemented to obtain higher conversions of tars. Based on the previous experiments conducted in the plasma-catalytic system with nickel as a catalyst, it can be concluded that nickel on the catalyst surface influenced the tar decomposition process. , The purpose of this work was to investigate the effects of the power of discharge, initial concentration of toluene, and the presence of G-0117 catalyst on the conversion of C 7 H 8 and the composition of outlet gas, as well as its calorific value. The goal of the research was to determine the durability of the catalyst activity during a process lasting approx.…”
Section: Introductionmentioning
confidence: 99%
“…Various plasma-catalytic systems are used. A catalyst may be located in a plasma zone [1][2][3][4][5][6][7], an electrode may be the catalyst [8,9], and often the catalyst is located outside the plasma zone [1,[10][11][12][13][14][15][16][17][18]. This way of placing the catalyst prevents the destruction of the catalyst by plasma and the disturbance of the discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Polish Journal of Chemical Technology, 23, 3, [24][25][26][27][28][29]10.2478/pjct-2021-0026 The research was conducted using 1500, 1750 and 2000 W of discharge power. Power range of the reactor was limited due to plasma discharge being unstable below 1500 W and 2000 W being its highest achievable value.…”
Section: Methodsmentioning
confidence: 99%